Targeting Cancer Stem Cells and Their Niche: Current Therapeutic Implications and Challenges in Pancreatic Cancer - Jiangang Zhao; Jiahui Li; Hans A. Schlößer; Felix Popp; Marie Christine Popp; Hakan Alakus; Karl-Walter Jauch; Christiane J. Bruns; Yue Zhao (Stem Cells International)
Cancer stem cells (CSCs) have been identified as a subpopulation of stem-like cancer cells with the ability of self-renewal and differentiation in hematological malignancies and solid tumors. Pancreatic cancer is one of the most lethal cancers worldwide. CSCs are thought to be responsible for cancer initiation, progression, metastasis, chemoresistance, and recurrence in pancreatic cancer. In this review, we summarize the characteristics of pancreatic CSCs and discuss the mechanisms involved in resistance to chemotherapy, the interactions with the niche, and the potential role in cancer immunoediting. We propose that immunotherapy targeting pancreatic CSCs, in combination with targeting the niche components, may provide a novel treatment strategy to eradicate pancreatic CSCs and hence improve outcomes in pancreatic cancer.